APPLICATION OF ULTRASOUND NAVIGATION FOR VENOUS ACCESS TO PATIENTS WITH ACUTE HEART FAILURE - A. K. Koyirov; S. R. Kenjaev; M. S. Mirmaksudov; A. A. Shukrullayev; Z. A. Kambarova (Евразийский Кардиологический Журнал)
Central vein catheterization is a widely used method vascular access for infusion therapy for recovery of circulating blood volume, monitoring of indicators hemodynamics, drug administration, etc. According to A.A. Bunyatyan (2009) for one year in the world, up to 15 million central venous catheters. According to a number of foreign authors, mechanical complications in central venous catheterization occur in 5-19 %o of cases (DavidC. McGee, Michael K.Gould 2003) Aim. To study reduce the incidence of mechanical complications in puncture and catheterization of the internal jugular and femoral veins using ultrasound navigation.